2013
DOI: 10.1007/s11095-013-1222-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Human Oral Bioavailability for Pharmaceutical Drugs by Using Various Cheminformatics Approaches

Abstract: Purpose Oral bioavailability (%F) is a key factor that determines the fate of a new drug in clinical trials. Traditionally, %F is measured using costly and time -consuming experimental tests. Developing computational models to evaluate the %F of new drugs before they are synthesized would be beneficial in the drug discovery process. Methods We employed Combinatorial Quantitative Structure-Activity Relationship approach to develop several computational %F models. We compiled a %F dataset of 995 drugs from pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 40 publications
(52 reference statements)
1
85
0
1
Order By: Relevance
“…Our previous studies showed that using hybrid descriptors, which are the combinations of chemical and biological descriptors, showed superior results compared to traditional QSAR models only based on chemical descriptors (23,37,38). The predictivity of hybrid modes is higher than the traditional QSAR models and the analysis of chemical-biological descriptor patterns in resulting models can reveal the relevant chemical biological mechanisms of target activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that using hybrid descriptors, which are the combinations of chemical and biological descriptors, showed superior results compared to traditional QSAR models only based on chemical descriptors (23,37,38). The predictivity of hybrid modes is higher than the traditional QSAR models and the analysis of chemical-biological descriptor patterns in resulting models can reveal the relevant chemical biological mechanisms of target activities.…”
Section: Resultsmentioning
confidence: 99%
“…An extra consensus QSAR model was then generated by averaging predictions of the three individual models. The development and application of consensus QSAR models have been reported in our previous publications (2123). …”
Section: Methodsmentioning
confidence: 99%
“…The rule states that an orally active drug has no more than one violation of the following criteria: (i) no more than five hydrogen bond donors, (ii) no more than ten hydrogen bond acceptors, (iii) a molecular mass less than 500 Da, and, finally, (iv) an octanol-water partition coefficient logP not greater than 5 (Lipinski et al 1997). This rule has been subsequently completed or amended by many authors to try to improve prediction models (Bergstrom et al 2014, Bhal et al 2007, Deconinck et al 2007, Gozalbes et al 2011, Kim et al 2014, Kujawski et al 2012, Palm et al 1997, Talevi et al 2011, van de Waterbeemd et al 2003, Veber et al 2002, Winiwarter et al 2003, Winiwarter et al 1998. To our knowledge, this approach was never or rarely developed in plant physiology to evaluate the capacity of a chemical to passively cross the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…All users can download publicly available models from Chembench, while only registered users can save, store, and download their personal models on Chembench. Currently, there are 124 publicly available predictors on Chembench that can either be downloaded or used for virtual screening (See Prediction), including, for example, predictors of the human intestinal transporter inhibition, 41 human oral bioavailability, 42 human plasma protein binding, 43 stress response and nuclear receptor signaling toxicity assays. 44 A full list of publicly available predictors can be found in the Supporting Information.…”
Section: Chembench Environmentmentioning
confidence: 99%